Crumbling edifice - "Kapur, V.P" (New Delhi, 2003)
Based on his vast and varied experience spanning over 34 years in the IPS, V. P. Kapur vividly brings out the gradual crumbling of the edifice of police administration, rule of law and criminal justice system in the country.
Keywords: Police Officer-thoughts and experiences